PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR IPAS SISWA PADA TOPIK INDONESIAKU KAYA ALAMNYA DI KELAS V SDN 028289 BINJAI - Tirana, Bella Vascha; Sitohang, Risma; Tamba, Robenhart; Unita Manurung, Imelda Free; Tambunan, Husna Parluhutan (Universitas Negeri Medan, 2024)
This research aims to find out and describe whether there is an influence of applying the discovery learning model in science and science lessons in improving the learning outcomes of class V students at SDN 028289 Binjai. This research was conducted at SDN 028289 Binjai in the 2023/2024 Academic Year. The type of research used is experimental research with a quasi-experimental research design. This research used two samples consisting of two classes, namely class V-A as the control class and class V-C as the experimental class with 20 students each. This research uses multiple choice test instruments to measure student learning outcomes and non-test instruments in the form of observations and interviews. The results of this research show that the discovery learning model has an influence in improving students' science learning outcomes as shown through the results of hypothesis test analysis which obtained a significance value of 0.000, which means it is smaller than 0.05 (0.000<0.05). This shows that Ho is rejected and Ha is accepted, so it can be concluded that the application of the discovery learning model can improve students' science and social learning outcomes.Keywords: Discovery Learning Model, Science and Social Learning, Outcomes Learning